Effects of pore diameters on phase, oxidation resistance, and thermal shock resistance of the porous Si2N2O ceramics. Issue 5 (2nd February 2017) - Lin, Shaojie; Ye, Feng; Ding, Junjie; Yang, Chunping; Ma, Jie; Dong, Shangli; Liu, Qiang
Abstract: Porous silicon oxynitride (Si2 N2 O) ceramics were prepared by gas pressure sintering at 1650°C for 2 hour under 1.5 MPa N2 in two different powder beds, that is, h‐BN/Si3 N4 or h‐BN/(Si3 N4 + SiO2 ). Effects of the gaseous atmosphere in the powder bed and the pore diameter in the ceramics on formation of the Si2 N2 O phase and the oxidation resistance of the sintered porous ceramics were investigated. Results showed that presence of the gaseous SiO in the powder bed played a crucial role in suppressing decomposition of the Si2 N2 O phase at the outer surface of the material. Permeability of the gaseous substances was decreased when the pore diameter was small, to affect the phase composition and the oxidation behavior of the porous Si2 N2 O ceramics. The oxidation weight gain curves of the porous Si2 N2 O ceramics fitted the asymptotic law. No significant changes in the dielectric constant of the Si2 N2 O ceramics were observed after oxidation at 1000°C‐1200°C for up to 30 minutes, whereas the dielectric loss tangent was reduced by oxidation due to formation of SiO2 . The as‐obtained porous Si2 N2 O ceramics could withstand a highest thermal shock of 1200°C when the outer surface could be sealed by the oxidation‐derived SiO2 layer.